Entangled empires: the Anglo-Iberian Atlantic, 1500-1830 - Cañizares-Esguerra, Jorge (University of Pennsylvania Press, 2018)
The Anglo-Iberian Atlantic as a hemispheric system? : English merchants navigating the Iberian Atlantic / Mark Sheaves -- Agents of empire : Africans and the origins of English colonialism in the Americas / Michael Guasco -- Empires on drugs : pharmaceutical go-betweens and the Anglo-Portuguese alliance / Benjamin Breen -- Marrying utopia : Mary and Philip, Richard Eden, and the English alchemy of Spanish Peru / Christopher Heaney -- The pegs of a wider frame : Jewish merchants in Anglo-Iberian trade / Holly Snyder -- Entangled Irishman : George Dawson Flinter and Anglo-Spanish imperial rivalry / Christopher Schmidt-Nowara -- Planters and powerbrokers : George J.F. Clarke, Interracial Love, and allegiance in the revolutionary circum-Caribbean / Cameron B. Strang -- The "Iberian" justifications of territorial possession by pilgrims and Puritans in the colonization of America / Jorge Cañizares-Esguerra -- "As the Spaniards have always done" : the legacy of Florida's missions for Carolina Indian relations and the origins of the Yamasee War / Bradley Dixon -- Reluctant petitioners : English officials and the Spanish Caribbean / April Hatfield -- Enabling, implementing, experiencing entanglement : empires, sailors, and coastal peoples in the British-Spanish Caribbean / Ernesto Bassi -- The Seven Years' War and the globalization of Anglo-Iberian imperial entanglement : the view from Manila / Kristie Flannery